Dasar keselamatan dan pertahanan Malaysia: warisan penjajahan dan era pasca kemerdekaan - Mohd Rizal Mohd Yaakop, (Penerbit UKM, 2007)
This article discusses Malay(si)a’s defence and security policy since independence, with a focus on the separation between internal security and external defence. After independence, Malayan leaders brought the country into an alliance with the British, while continuing its emergency laws. The paper also focuses on the strategies of the leaders to preserve political security by embarking on military cooperation with the British and by managing the nation’s internal security.